Synthesis, Optimization, and Large-Scale Preparation of the Low-Dose Central Nervous System-Penetrant BACE1 Inhibitor LY3202626 via a [3 + 2] Nitrone Cycloaddition - Garcia-Losada, Pablo; DeBaillie, Amy C; Eugenio de Diego, Jose; Green, Steven J; Hansen, Marvin M; Jaramillo, Carlos; Johnson, Matt; Kaoudi, Talbi; Li, Jiuyuan; Lindsay-Scott, Peter J; Mateos, Carlos; Mergott, Dustin J; et al. (Organic process research & development, 2020)
Herein we report a summary of the synthetic development of LY3202626 from the initial discovery route to a final route that was scaled to make 150 kg. Key developments include the use of a [3 + 2] cyclization to set the cis ring junction of the formed isoxazoline, a one-pot thiazine formation, and three different ways to install the aniline: (1) Cu-catalyzed azide coupling and reduction, (2) nitration and reduction, and (3) Buchwald coupling with acetamide.